2018
DOI: 10.1159/000492226
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of TAK-828F, a Potent and Selective Retinoid-Related Orphan Receptor Gamma t Inverse Agonist

Abstract: Background/Aims: Retinoid-related orphan receptor gamma t (RORγt) is a master regulator of T helper 17 cells that plays a pivotal role in the production of inflammatory cytokines including interleukin (IL)-17. Therefore, RORγt has attracted much attention as a target receptor for the treatment of inflammatory diseases including rheumatoid arthritis, multiple sclerosis, inflammatory bowel diseases, and psoriasis. This study aims to characterize TAK-828F, a potent and selective RORγt inverse agonist. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We also tested the selectivity against other nuclear receptors in a panel of cellular reporter assays (Invitrogen) and found that compound 10 was a selective RORγt inverse agonist with >800fold selectivity over the other 20 nuclear receptors in both agonist and antagonist modes. 25 In order to determine if our RORγt inverse agonists could modulate the cytokine production through the suppression of differentiation and activation of Th17 and Th1/17 cells, we evaluated the in vivo PD efficacy in the mouse IL-23-induced cytokine expression model. Compound 10 showed robust and dose-dependent inhibition of IL-17A expression after oral administration at 0.3, 1, and 3 mg/kg b.i.d.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested the selectivity against other nuclear receptors in a panel of cellular reporter assays (Invitrogen) and found that compound 10 was a selective RORγt inverse agonist with >800fold selectivity over the other 20 nuclear receptors in both agonist and antagonist modes. 25 In order to determine if our RORγt inverse agonists could modulate the cytokine production through the suppression of differentiation and activation of Th17 and Th1/17 cells, we evaluated the in vivo PD efficacy in the mouse IL-23-induced cytokine expression model. Compound 10 showed robust and dose-dependent inhibition of IL-17A expression after oral administration at 0.3, 1, and 3 mg/kg b.i.d.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2-(6-Methoxypyridin-2-yl)ethanamine (25). Hydrazine monohydrate (24.9 mL, 514 mmol) was added to a solution of 24 (29.0 g, 103 mmol) in EtOH (300 mL) at room temperature.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Compound 15 (TAK-828F) has potent RORγt inverse agonistic activity, excellent selectivity, and an improved PK/PD profile (LLE, 4.68; IC 50 = 0.002 μM in a binding assay; IC 50 = 0.006 μM in a reporter gene assay; ED 80 = 0.5 mg/kg b.i.d. in IL-17A PD model, F = 96% and AUC 0–8h , 10076 μg·h/mL). Compound 15 reduces the production of Th17-related cytokines (IL-17, IL-17F, and IL-22) at 100 nM without affecting IFN-γ production in whole blood and shows a dose-dependent pharmacological effect in a naive T cell transfer mouse colitis model . In the EAE model, compound 15 displayed a 50% reduction in the clinical score upon oral dosing at 1 mg/kg b.i.d.…”
Section: Agonist Lock Untouched and Agonist Lock Touched Rorγt Invers...mentioning
confidence: 98%
“…10 ) [ 150 ]. The regulator suppressed the recruitment of SRC1 with IC 50 of 59 nM and blocked the transcription of RORγt with IC 50 of 9.5 nM [ 151 ]. In mouse model of EAE, the administration of TAK-828F (0.3−3 mg/kg) decreased the symptoms of EAE dose-dependently, and further study suggested that it reduced the Th17 cell-mediated inflammatory response via decreasing IL-17A production [ 152 ].…”
Section: Small-molecule Rorγt Inhibitors For Managing Inflammatory An...mentioning
confidence: 99%
“…As summarized in Table 3 [ [122] , [123] , [124] , [125] , [128] , [129] , [130] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , 145 , 146 , [150] , [151] , [152] , [153] , [154] , [159] , [160] , [161] , [162] , [163] , [164] , 166 , 167 , 169 , 170 ], numerous RORγt inhibitors (antagonists and inverse agonists) are actively being researched for the therapy of probable inflammatory disorders due to significance of RORγt in autoimmune and inflammatory diseases. Some of the reported RORγt inhibitors, such as JTE-451 (Retezorogant), BI730357 (Bevurogant), ABBV-157 (Cedirogant), RTA-1701 and AUR101, have also entered clinical trial evaluation ( Table 4 ) [ 121 , 139 , [171] , [172] , [173] , [174] , [175] , [176] , [177] , [178] , [179] , [180] , [181] , [182] , [183] , [184] , [185] , [186] ].…”
Section: Clinical Application Of Rorγt Inhibitorsmentioning
confidence: 99%